Speaking manner seen from pragamatic principles and Islamic perspective a case study of bella's character in twilight movie - Candra Putrie Rahmawati (Fak. Adab dan Ilmu budaya UIN Sunan Kalijaga, 2013)
Hardi/nr,c.1